Serum CXCL 9 as a Potential Biomarker for Patients with Ulcerative Colitis - Qusay, Mohammed A.; Zeiny, Sarmad M.H.; Al-Maraashi, Haider J.M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Ulcerative colitis (UC) is an inflammatory bowel disease restricted to the large intestine, characterized by superficial ulceration. It is a progressive and chronic disease requiring long-term treatment. Although its etiology remains unknown, it is suggested that environmental factors influence genetically susceptible individuals, leading to the onset of the disease. (C-X-C) ligand 9 is a chemokine that belongs to the CXC chemokine family, it plays a role in the differentiation of immune cells such as cytotoxic lymphocytes, natural killer T cells, and macrophages. Its interaction with its corresponding receptor CXCR3 which is expressed by a variety of cells such as effector T cells, CD8+ cytotoxic T cells, and macrophage, leads to stimulation of the production of IFN-γ and TNF-α and in turn, stimulates the production of Th1 chemokines which results in promoting the inflammation. Objectives: To assess the significance of serum chemokine (C-X-C) ligand 9 as a potential marker for identifying ulcerative colitis in adults with inflammatory bowel disease. Methods: This is a case-control study that included 50 patients diagnosed with UC, aged between 18 and 75 years, compared to 50 healthy controls, aged between 18 and 60 years. The study was conducted between November 2022 and March 2023, at the Gastroenterology and Hepatology Teaching Hospital at the Medical City Complex in Baghdad. The serum samples were analyzed using the Enzyme-Linked Immunosorbent Assay (ELISA) technique. Results: The mean ± SD in pg/ml of serum CXCL9 in the patient group was 26.9 ± 9.05 and in the control group was 6.4 ± 2.37 (p< 0.0001) which indicates a highly significant difference. Conclusion: CXCL 9 may be a biomarker for identifying ulcerative colitis. It can be used as a tool for measuring disease activity, in addition to the possibility of being a potential therapeutic target.